2002
DOI: 10.1080/02786820290092104
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Scavenging of Small Particles by Charged Droplets

Abstract: The trajectories of ne aerosol particles in the vicinity of a free falling collector droplet and their deposition on it were investigated numerically by solving the equations of motion of the particle and the droplet in quiescent air. The droplet was assumed to be charged to one half of the Rayleigh limit. The Coulomb, image, Stokes, inertial, and gravitational forces acting upon the particle near the droplet were taken into consideration in the equations of motion. The equations of the droplet motion were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…A number of studies have suggested that thermophoresis, diffusiophoresis, and electric charges may increase E(d p ,D p ) for particles in the 0.01−1 µm diameter range (e.g., Slinn and Hales, 1971;Grover et al, 1977;Wang et al, 1978;McGann and Jennings, 1991;Byrne and Jennings, 1993;Pranesha and Kamra, 1997;Tripathi and Harrison, 2001;Tinsley et al, 2000;Jaworek et al, 2002;Andronache, 2004;Chate, 2005;Andronache et al, 2006). Thermophoresis, which is caused by uneven heating of particles in ambient temperature gradients, drives particles towards evaporating and sublimating hydrometeors.…”
Section: Raindrop-particle Collection Efficiency E(d P D P )mentioning
confidence: 99%
“…A number of studies have suggested that thermophoresis, diffusiophoresis, and electric charges may increase E(d p ,D p ) for particles in the 0.01−1 µm diameter range (e.g., Slinn and Hales, 1971;Grover et al, 1977;Wang et al, 1978;McGann and Jennings, 1991;Byrne and Jennings, 1993;Pranesha and Kamra, 1997;Tripathi and Harrison, 2001;Tinsley et al, 2000;Jaworek et al, 2002;Andronache, 2004;Chate, 2005;Andronache et al, 2006). Thermophoresis, which is caused by uneven heating of particles in ambient temperature gradients, drives particles towards evaporating and sublimating hydrometeors.…”
Section: Raindrop-particle Collection Efficiency E(d P D P )mentioning
confidence: 99%
“…2), Schumann (1989) and McGann and Jennings (1991). One reason for discrepancy can be the electrical interaction between charged rain droplets and aerosol particles (Jaworek et al, 2002). An extensive analysis of the possible reasons for this discrepancy is given by Volken and Schumann (1993).…”
Section: Article In Pressmentioning
confidence: 99%
“…This applies to particles with diameter more than about 1 mm: For particles smaller than 1 mm Brownian diffusion is the main removal mechanism. The effect of electrical forces is often (McGann and Jennings, 1991;Byrne and Jennings, 1993;Jaworek et al, 2002) assumed to be one of the major sources of uncertainty in the calculations of scavenging coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…Elapsed-time evolutions of urban aerosols in the health hazardous mode (0.02 lm B D p B 0.1 lm) after 30 and (Table 1) 60 min thunderstorm rain in Figs. 2 and 3 support the notion that electrical and phoretic effects are most active in scavenging these particles (Jaworek et al 2002;Andronache 2004;Chate and Pranesha 2004;Chate 2005). Model study of Garcia et al (1994) illustrates that when compared to initial volume of respirable dust (before rain), it remains *60% after 12 h of drizzle (0.5 mm h -1 ) or 1 h of heavy rain (25 mm h -1 ).…”
Section: Resultsmentioning
confidence: 67%
“…The capture of aerosol number by falling raindrop takes place with Brownian diffusion, inertial impaction, diffusion-thermo-phoresis and electrical effects (Wang et al 2010). Beside strong electrical forces, on aerosols and raindrops during thunderstorm, rapid evaporation and condensation cause phoretic effects (Jaworek et al 2002;Andronache 2004;Chate 2005). Scavenging coefficients from measured aerosol size distribution changes by rain in different environments have been reported elsewhere (Davenport and Peters 1978;Laakso et al 2003;Chate and Pranesha 2004;Maria and Russell 2005;Andronache et al 2006).…”
Section: Introductionmentioning
confidence: 94%